Comparison of oocyte vitrification using a semi-automated or a manual closed system in human siblings: survival and transcriptomic analyses - Julie Barberet; Bastien Ducreux; Céline Bruno; Magali Guilleman; Raymond Simonot; Nicolas Lieury; Adrien Guilloteau; Déborah Bourc'his; Patricia Fauque (BMC, 2022)
Abstract Background Indications of oocyte vitrification increased substantially over the last decades for clinical and ethical reasons. A semi-automated vitrification system was recently developed making each act of vitrification reproducible. In this study, we evaluated the efficiency of the semi-automated technique of oocyte vitrification by survival rate, morphometric assessment and resistance to empty micro-injection gesture as compared with a manual method. Additionally, we intended to evaluate transcriptomic consequences of both techniques using single-cell RNA-seq technology. Results Post-warming survival rate, oocyte surfaces and resistance to empty micro-injection were comparable between semi-automated and manual vitrification groups. Both oocyte vitrification techniques showed limited differences in the resulting transcriptomic profile of sibling oocytes since only 5 differentially expressed genes were identified. Additionally, there was no difference in median transcript integrity number or percentage of mitochondrial DNA between the two groups. However, a total of 108 genes were differentially expressed between fresh and vitrified oocytes (FDR < 0.05) and showed over-represented of genes related to important cellular process. Conclusions Our results provide reassurance about the influence of semi-automation as compared with the manual vitrification method. Concerning oocyte vitrification itself, no tight common transcriptomic signature associated has been observed across studies. Trial registration NCT03570073.